2009
DOI: 10.1289/ehp.11350
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among Former Love Canal Residents

Abstract: BackgroundThe Love Canal is a rectangular 16-acre, 10-ft deep chemical waste landfill situated in a residential neighborhood in Niagara Falls, New York. This seriously contaminated site first came to public attention in 1978. No studies have examined mortality in the former residents of the Love Canal neighborhood (LC).ObjectiveThe aim of this study was to describe the mortality experience of the former LC residents from the years 1979–1996.MethodsFrom 1978 to 1982, 6,181 former LC residents were interviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Table 3. The average lengths of (i) (SMR -lower confidence limit) and (ii) (upper confidence limit -SMR) of the various 95% confidence intervals obtained by simulating 1000 SMRs based on P 1 and Q = 1. elevated (5)(6)(7)(8)(9), significantly elevated (10)(11)(12)(13)(14), high (15)(16)(17)(18)(19) and very high (20-100). The probability of death of a patient assuming the performance of an average surgeon, x 0 (and represented as x) is calculated using Equation (6) and x is assumed to be the true probability of death in the study.…”
Section: Effect Of Risk Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3. The average lengths of (i) (SMR -lower confidence limit) and (ii) (upper confidence limit -SMR) of the various 95% confidence intervals obtained by simulating 1000 SMRs based on P 1 and Q = 1. elevated (5)(6)(7)(8)(9), significantly elevated (10)(11)(12)(13)(14), high (15)(16)(17)(18)(19) and very high (20-100). The probability of death of a patient assuming the performance of an average surgeon, x 0 (and represented as x) is calculated using Equation (6) and x is assumed to be the true probability of death in the study.…”
Section: Effect Of Risk Distributionmentioning
confidence: 99%
“…The SMR is described in many biostatistics textbooks, for examples, Pagano and Gauvreau [26], Forthofer et al [12], Armitage et al [2], Antonisamy et al [1] and Rosner [30]. It is frequently used in various fields including occupational epidemiology [23,29,36], cancer studies [3,7,14,15,22], heart studies [16,17,25] and medical care [6,13,31,32,34,40].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Gensburg et al (2009) summarize the mortality experience of > 6,100 former residents of Love Canal, New York, over the period 1979–1996. Love Canal became a household word 30 years ago when outraged residents, led by Lois Gibbs and the Love Canal Homeowners Association, demanded attention to the apparent adverse effects of hazardous waste exposures on their children’s health ( Boston University School of Public Health 2004 ).…”
mentioning
confidence: 99%
“…The trust fund created by this legislation paid for cleanup of the most dangerous contamination sites, and its amendments and reauthorization in 1986 created the Agency for Toxic Substances and Disease Registry (ATSDR; Atlanta, GA) to conduct health studies of residents in exposed communities, among other things. The New York State Department of Health used funds from the ATSDR to pay, in part, for the study by Gensburg et al (2009) .…”
mentioning
confidence: 99%
“…199 The study assessing death rates and causes found an increased mortality ratio for acute myocardial infarction when comparing the Love Canal cohort to New York State. 200 Additionally, a greater than expected incidence of bladder and kidney cancer was observed when comparing cancer incidence in former Love Canal residents to New York State residents, though the differences were not statistically significant. 201 The Love Canal cohort is still relatively young and the mortality and cancer incidence findings may change as the community ages.…”
Section: Developmental Effectsmentioning
confidence: 86%